ZINC ADSORPTION IN DIFFERENT CALCAREOUS SOILS - RAMADHAN, PAYIZAN IHSAN; MEHMEDANY, LAZKEEN AHMED MERWEEN (Journal of Duhok University, 2020)
Zinc adsorption was studied for ten selective representative soils according the difference amount ofclay content, calcium carbonate and organic matter in Duhok governorate, Iraqi-Kurdistan region included (Kanimasi-1&2, Batofa, Zakho, Assih, Semeel, Khanke, Faydi, Zawita and Bamarny locations). Samples were air dried and sieved through a 2-mm sieve to study the physical and chemical characteristics of the soils, forms of zinc and it’s adsorption. Results showed the soluble, DTPAextractable zinc (available), CaCl2 extractable zinc (exchangeable) and total zinc ranged between (0.29 –0.94), (0.88 – 1.64), (1.71 – 2.05), and (12.25 – 56.15) mg kg-1respectively. Negative significant correlation found between soluble zinc with pH, also negative significant correlation found between DTPA extractable zinc with exchangeable potassium, bicarbonate and available phosphorus but positive significant correlation found between CaCl2 extractable zinc with pH, total–Zn negatively affected with pH and positively with HCO3 and sand. Results demonstrated that by increasing added zinc concentration to studied soil zinc will be adsorbed zinc adsorbed greatly at temperature 25°C and 48°C. In general total zinc adsorbed at 25C° in six concentrations was less than zinc adsorbed at 48C°. At temperatures 25°Cand 48°C the high total amount of zinc adsorbed found in the soil of Zawita and Zakho respectively, but the lower total zinc adsorbed observed in soil of Batofa and Kani masi-2. The quantity of adsorption affected positively by presence of clay, calcium carbonate, active calcium carbonate and cation exchange capacity and negatively affected by the ion concentration of bicarbonate, calcium, potassium, organic matter and sand content.